Substantiviske Komplekse Ord Med Subkonfikser I Moderne Dansk - Rajnik, Eugeniusz (Folia Scandinavica Posnaniensia, 2014)
The article discusses various definitions of the Danish term konfiks (præ- and subkonfiks) as well as other, more recently coined, terms (e.g. komplekse ord) used within Danish, Norwegian, Swedish and German word formation. Section 3 includes a list of nominal subkonfikser present in modern Danish as well as examples thereof. The listed nouns have been classified based on whether their first component can exist independently or not. The summary section includes, amongst others, the productivity of subkonfikser as well as various restrictions regarding their use.